211k views
5 votes
Solve: (3x^2-y)dx + (4y^3-x)dy =0 and find the solution passing through (1,1).

1 Answer

3 votes

Explanation:

The given equation is


(3x^(2)-y)dx+(4y^(3)-x)dy=0\\M(x,y)dx+N(x,y)dy=0

As a check for exactness we have


(\partial N)/(\partial x)=(\partial M)/(\partial y)\\\\\therefore (\partial N)/(\partial x)=(\partial (4y^(3)-x))/(\partial x) =-1\\\\(\partial M)/(\partial y)=(\partial (3x^(3)-y))/(\partial y) =-1\\\\\therefore (\partial N)/(\partial x)=(\partial M)/(\partial y)=-1

Hence the given equation is an exact differential equation and thus the solution is given by

thus the solution is given by


u(x,y)=\int M(x,y)\partial x+\phi (y)\\\\u(x,y)=\int (3x^(2)-y)\partial x+\phi (y,c)\\\\u(x,y)=x^(3)-xy+\phi (y,c)\\\\

Similarly we have


u(x,y)=\int N(x,y)\partial y+\phi (x,c)\\\\u(x,y)=\int (4y^(3)-x)\partial y+\phi (x,c)\\\\u(x,y)=y^(4)-xy+\phi (x,c)\\\\

Comparing both the solutions we infer


\phi (x,c)=x^(3)+c

Hence the solution becomes


u(x,y)=x^(3)+y^(4)-xy=c

given boundary condition is that it passes through (1,1) hence


1^(3)+1^(4)-1=c\\\\\therefore c=1

thus solution is


u(x,y)=x^(3)+y^(4)-xy=1

User Elliott Slaughter
by
5.3k points